2012
DOI: 10.1002/bip.22085
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulation studies on the effect of one residue chain staggering on the structure and stability of heterotrimeric collagen‐like peptides with interruption

Abstract: A systematic molecular dynamics (MD) simulation has been carried out on collagen-like peptides with different combinations of interruptions in the Gly-X(AA) -Y(AA) repeats. Although experimental studies have been carried out to elucidate the structural consequences of homotrimeric collagen-like peptides, this is the first report on the structural effect on the heterotrimeric models with G4G and G1G breaks present simultaneously in the constituent chains with difference in one residue chain staggering. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 131 publications
0
10
0
Order By: Relevance
“…While experimental techniques have provided much of the available structural information, computer simulations of biological systems and of membrane proteins in particular have been able to provide critical information about the dynamics and energetics of these macromolecules. 46 …”
Section: Introductionmentioning
confidence: 99%
“…While experimental techniques have provided much of the available structural information, computer simulations of biological systems and of membrane proteins in particular have been able to provide critical information about the dynamics and energetics of these macromolecules. 46 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, investigators have constructed fragments of collagen molecule to investigate problems that could not be solved by traditional studies. Singam et al reported that the structural effect on the heterotrimeric models with G4G and G1G breaks present simultaneously in the constituent chains with difference in one residue chain staggering and found that the structural parameters of the hydrogen-bonding pattern differ significantly due to the difference in the staggering of chains . Almora-Barrios et al used the Materials Studio, version 4.0 package to construct three chains of [ − OOC-(GLY-PRO-HYP) 10 -NH 2 + ] 3 folded into a triple-helix collagen fragment.…”
Section: Introductionmentioning
confidence: 99%
“…Singam et al reported that the structural effect on the heterotrimeric models with G4G and G1G breaks present simultaneously in the constituent chains with difference in one residue chain staggering and found that the structural parameters of the hydrogen-bonding pattern differ significantly due to the difference in the staggering of chains. 40 Almora-Barrios et al 41 used the Materials Studio, version 4.0 package to construct three chains of [ − OOC-(GLY-PRO-HYP) 10 -NH 2 + ] 3 folded into a triple-helix collagen fragment. By immersing the constructed collagen in a stoichiometric solution of Ca + , PO 4 3− , and OH − ions, they observed the formation of calcium phosphate clusters at the collagen template.…”
Section: Introductionmentioning
confidence: 99%
“…Cartesian PCA (cPCA) and internal coordinate PCA methods are frequently used in characterizing the folding and unfolding of proteins [16, 17] and understanding the opening and closing mechanisms within proteins, including ion channel proteins [1821]. More generally, PCA is routinely employed to elucidate the variance in the distribution of sampled conformations in a molecular dynamics trajectory [22]. Conformational dynamics of a protein upon ligand binding has also been investigated with a PCA approach [23].…”
Section: Introductionmentioning
confidence: 99%